PSXII-36 Effectiveness of sericea lespedeza leaf meal pellets and whole plant pellets for natural control of gastrointestinal nematodes and coccidia in goats. (7th December 2018) - Terrill, T; Dykes, G; Singh, A; Greer-Mapson, L; Owen, V; Miller, J; Whitley, N
Abstract: Lespedeza cuneata) has been extensively studied in sheep and goat feeding trials, but there has never been a direct comparison made between whole plant and leaf only pellets. A study was completed with goats to test the anti-parasitic bioactivity of leaf only and whole plant SL pellets compared with a commercially-available pellet. Twenty-seven mature (18 month-old) Spanish bucks were fed diets consisting of 50% pellets and 50% supplement in individual pens for a 6-week trial at the Fort Valley State University Agricultural Research Station in Fort Valley, GA. Diets were balanced for protein and energy. Fecal samples were taken from individual animals weekly to determine GIN eggs per gram (EPG) and coccidial oocysts per gram (OPG). Blood samples were taken weekly to determine packed cell volume (PCV). Adult worms were recovered for counting and identification to species at the end of the study. Both of the pelleted SL rations reduced EPG (P < 0.06) relative to the kids fed the control ration. There was a treatment x time interaction (P < 0.01) for OPG, with lower values on Days 7 to 42 relative to Day 0 for goats on either of pelleted SL diets, while OPG for control animals did not change over time. Blood PCV and adult worm numbers were not affected by treatment diets in this study. When fed at 50% of the diet, SL leaf meal and whole plant meal pellets were equally effective against GIN egg and Eimeria spp. oocyst production in young kids. Pelleted SL has potential as an alternative to anthelmintic drugs for small ruminant parasite control.